2020
DOI: 10.1017/jog.2020.3
|View full text |Cite
|
Sign up to set email alerts
|

An ~1899 glacier inventory for Nordland, northern Norway, produced from historical maps

Abstract: Glaciers depicted on old maps reveal their historical extents, before the advent of aerial and satellite remote sensing. Digital glacier inventories produced from these maps can be employed in assessments of centennial-scale glacier change. This study reconstructs the ~1899 (covering the period 1882–1916) glacier extent in Nordland, northern Norway, from historical gradteigskart maps, with an emphasis on examining the accuracy of the mapped glaciers. Glacier outlines were digitised from georectified scans of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
1
8
1
Order By: Relevance
“…that region receded in area by 47% between ca. 1899 and 2000 (Weber et al 2020). This value is similar to Langfjordjøkelen's 50% area reduction between 1925 and 2006 but represents a considerably longer measurement interval.…”
Section: Comparison Of Centennial-scale Glacier Change Across Norwaysupporting
confidence: 74%
See 3 more Smart Citations
“…that region receded in area by 47% between ca. 1899 and 2000 (Weber et al 2020). This value is similar to Langfjordjøkelen's 50% area reduction between 1925 and 2006 but represents a considerably longer measurement interval.…”
Section: Comparison Of Centennial-scale Glacier Change Across Norwaysupporting
confidence: 74%
“…This value is similar to Langfjordjøkelen's 50% area reduction between 1925 and 2006 but represents a considerably longer measurement interval. When icefield-type glaciers were compared alone, the nine largest Nordland icefields decreased in area by only 27% in the period 1899-2000 (Weber et al 2020), which is only about half the percentage change that we observed at Langfjordjøkelen. Stokes et al (2018) assessed long-term glacier change in Lyngen since the local LIA maxima in ca.…”
Section: Comparison Of Centennial-scale Glacier Change Across Norwaycontrasting
confidence: 58%
See 2 more Smart Citations
“…Topographic maps older than 1936 have been used to draw profiles or to calculate glacier extent (Liestøl, 1969; Nuttall and others, 1997; Pälli and others, 2003; Flink and others, 2015, 2018). However, the associated errors are large and sometimes difficult to quantify, although the workflow suggested by Weber and others (2020) may help in standardising these errors. Since no similar historic terrestrial reconstructions have been done on Svalbard before 1936, the results of this study lack a good comparison.…”
Section: Discussionmentioning
confidence: 99%